Optimization of Ammonia Co-Firing Networks - Raymond R. Tan; Kathleen B. Aviso; Maria Victoria Migo-Sumagang; Luis F. Razon (Chemical Engineering Transactions, 2024)
Ammonia produced using renewable inputs, or green ammonia, is a promising fuel for deep decarbonization in the industrial, transportation, and power generation sectors. Like green hydrogen, it is a carbon-neutral energy carrier without the associated challenges in handling and storage. The use of pure ammonia in combustion systems entails extensive retrofits or investment in new, dedicated systems due to significant changes in flame speed and air-fuel ratio compared to natural gas. On the other hand, ammonia can be blended with natural gas to achieve partial decarbonization with minimal modifications to combustion systems. The blending limits depend on the specific characteristics of the equipment used as well as the risk appetite of firms to accept some degree of performance loss. In this work, a mathematical programming model is developed to optimize ammonia co-firing networks consisting of ammonia production facilities acting as sources, and ammonia-using plants acting as sinks. Each source has a specified capacity and carbon footprint per unit of product; each sink has a specified upper limit on ammonia demand based on its self-defined blending limit. The model is formulated to allocate the ammonia supply to minimize aggregate carbon emissions. Two representative case studies are used to illustrate the model’s capabilities, with system-wide substitution rates of 17.2 % and 15.1 % being achieved.